Content of macro- and microelements in rats with experimental autoimmune thyroiditis and under the influence of lemna minor - Kononenko, Alevtyna; Kravchenko, Vira (ScienceRise: Biological Science, 2024)
The aim was to study the effect of aqueous extract and 30 % alcohol tincture of Lemna minor frond (AELM and TLM) on the content of macro- and microelements in rats with experimental autoimmune thyroiditis. Materials and methods. The effect of AELM and TLM was studied in a model of experimental autoimmune thyroiditis in rats, induced by immunization with human thyroid antigen. The serum levels of total thyroxine, total triiodothyronine, antibodies to thyroglobulin, antibodies to thyroperoxidase, and concentrations of macro- and microelements were studied. Results. The development of experimental autoimmune thyroiditis led to a decrease in the content of total thyroxine and antibodies to thyroperoxidase in the blood serum, an increase in the content of antibodies to thyroglobulin and a decrease in the concentrations of sodium, chlorine, potassium phosphorus, zinc, copper, iron and magnesium. It was found that the use of AELM and TLM against the background of autoimmune thyroiditis led to the restoration of T4 and elemental balance in rats, which was manifested in an increase in the content of sodium, chlorine, phosphorus, magnesium, zinc, iron, copper and calcium in the blood serum. It was also shown that TLM had a more powerful effect on the normalisation of the content of such elements as chlorine, potassium, copper and zinc. The obtained effect of AELM and TLM on the content of macro- and microelements in the blood serum of animals with experimental AIT can be explained by their positive effect on the functional activity of the thyroid gland. The studied extract and tincture may also affect other physiological and biochemical processes due to the content of macro- and microelements and other biologically active substances, which requires further research. Conclusions. Administration of AELM and TLM to rats with experimental AIT contributed to lowering the level of Anti-TG and restoring the thyroid and elemental status in the animals’ blood serum. The obtained research data allow us to recommend AELM and TLM as a regulator of the elemental status of the body in case of changes in thyroid function